Constituição do ensino superior de Educação Física no Espírito Santo (1931-1972) - Patricia Pereira de Souza (2004)
This research aimed to study the history of the Physical Education and Sports Center ("Centro de Educação Física e Desportos", or CEFD) of the Universidade Federal do Espírito Santo (UFES). This study focused on the analysis of the constitution of higher education in physical educationin the state of Espírito Santo through the teaching practices of the key teachers in charge of the subjects of those areas considered as part of the Gymnastics Sports Sector, as defined by Technical Report nr. 864/69. These subjects were chosen because they were those that suffered greater díffículties and modifications in the Espírito Santo Physical Education School due to lack of space, time and didactic materiais at several points, the teachers responsible having had to elaborate means of imparting their classes even in unsuitable spaces. The main focus af the work was: how did the .teaching and the day·to-day teaching practices shape themselves at the CEFD-UFES from the 1930s to the '1970's, considering the changes which took place all through its historic process, from the foundation of the Espírito Santo Physical Education School to the inauguration of the CEFD-UFES? Oral history was the methodological procedure which guided the selection of sources. Selection of interviewees was done by means of function files and payroll sheets obtained at the DRH-UFES and in the archives of the CEFD-UFES. Six teachers were interviewed. In addition to oral sources, various other sources were consulted, such as official documents, resumes, statutes, bylaws and newspapers. The research led to the conclusion that although the course programs, dnd curricula have their worth, it is the physical spaces and the human and didatic materials that guided the institution's teaching practices. Among relevant figures, teatcher Aloyr Queiroz de Araújo stood out, as his life history is linked to the history both of CEFD-UFES and of physical educatíon teaching in Espírito Santo State. As to the conception of physical education and of teacher formation in the eyes of those herein treated as "forming teachers", a nationalistic and technical- professional vision prevailed. The School had in its staff both teachers who followed the existing guidelines and obeyed rules and regulations, as well as those who sought to incite the students to think and elaborate personal opinions.